Students’ Motivation in Learning English Listening Skills Independently - Ahmad, Annisa; Zulfah; Mujahidah; Nur Asiza (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
The achievement of English listening skills among students still requires serious attention, with many students finding these skills difficult due to various factors, including lack of practice and motivation. This study aims to measure students' level of motivation in learning English listening skills independently. The methodology used was a descriptive quantitative approach with a survey design, involving 28 students from the English Education study program at Parepare State Islamic Institute. Data was collected through a questionnaire consisting of 11 statements using a Likert scale. The results showed that the majority of students were highly motivated in learning English listening skills independently, driven by their ability to set personal learning goals and access to a variety of engaging resources, including materials and media. Nonetheless, some students showed challenges in time management and lack of external support, which may hinder their motivation. These findings underscore the importance of creating a supportive learning environment and utilizing technology to improve students' motivation and learning outcomes in English listening skills.